2013
DOI: 10.1002/meet.14505001059
|View full text |Cite
|
Sign up to set email alerts
|

Lost while searching: Difficulties in information seeking among end‐user programmers

Abstract: End‐user programmers, those who write code but lack formal training in computer science, are often reliant on various tools such as API documentation or searching the Web for information in order to complete a specific task. This study examines the information foraging behaviors of a group of web and graphic designers engaged in a series of code modification tasks. We find that users were largely unsuccessful in their foraging activities, with few information seeking events resulting in noticeable changes to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…(P1), Discussion. Prior work on end-users' example search behaviors showed that they may not know how to articulate what it is they want to see in examples [9]. Our analysis found similar results, that novices may also encounter difficulties expressing the functionality they need in an example, and instead search for items that they associate with that functionality (e.g.…”
Section: Search Barrier: How Do I Explain the Example I Want?supporting
confidence: 63%
“…(P1), Discussion. Prior work on end-users' example search behaviors showed that they may not know how to articulate what it is they want to see in examples [9]. Our analysis found similar results, that novices may also encounter difficulties expressing the functionality they need in an example, and instead search for items that they associate with that functionality (e.g.…”
Section: Search Barrier: How Do I Explain the Example I Want?supporting
confidence: 63%
“…However, if a part of the provided code is unclear, it is difficult for them to know what to search for. Additionally, general purpose search engines may not perform well for code queries (Dorn et al 2013). For instance, if a student in a C programming course sees a line like int * p = &i;, he might wonder what * or & mean, but these special characters might be ignored by such a search engine.…”
Section: Ide Plugin and Hashtagsmentioning
confidence: 99%
“…In addition, the assumption that students know how to perform a search effectively is often not fulfilled, as they might lack prior experience with advanced search functionalities (Mavridis et al 2017;Paynter 2015). The level of expertise and the search accuracy are often positively correlated (Dorn et al 2013). As there is usually no explicit link between a task and the relevant learning material, it is especially challenging for novices to know what to search for, as already expressed in Meno's paradox of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that there are critical information retrieval skills necessary to successfully using online resources about computing. For example, the use of Q&A sites and code search requires people to learn search and query reformulation skills, which are non-obvious to novices (Dorn et al, 2013). DiSalvo discovered that parents looking for computer science educational resources for their children had trouble obtaining good results from what they thought were reasonable search queries (DiSalvo, 2014).…”
Section: Finding and Using Online Resourcesmentioning
confidence: 99%